Research Methods in the Study of Substance Abuse - VanGeest, Jonathan B.; Johnson, Timothy P.; Alemagno, Sonia A. (Springer International Publishing : Imprint: Springer, 2017)
This authoritative handbook reviews the most widely-used methods for studying the use and abuse of alcohol and illegal drugs. Its thorough coverage spans the range of quantitative, qualitative, and mixed-method approaches to documenting and measuring the complex psychological, behavioral, and physical experience of substance misuse and dependence, to ensure valid, useful results. Experts discuss special issues and considerations for conducting ethical research with specialized populations, including youth, inmates, and the LGBT community. Throughout these chapters, contributors demonstrate the multidisciplinary nature of substance abuse research, with emphasis on professional ethics and the critical role of research in developing best practices and effective policy for prevention and treatment. Among the topics covered: - Transdisciplinary research perspective: a theoretical framework for substance abuse research. - Longitudinal methods in substance use research - Considerations in blending qualitative and quantitative components in substance abuse research - The use of biological measures in social research on drug misuse - Using surveys to study substance use behavior - Applications of GIS to inform substance abuse research and interventions - Evaluating substance use prevention and treatment programs Research Methods in the Study of Substance Abuse is an essential resource for health services and public health professionals, policymakers, and researchers working and training in the field of addiction. It encourages the rigor and understanding necessary to address widespread social and public health concerns.
Keywords: Social sciences.; Public health.; Epidemiology.; Sociology -- Research.; elektronické knihy; electronic books